High density plantation in apple - A highly remunerative enterprise - Mir, J I; Sharma, O C; Raja, W H; Sami-Ullah, S; Raja, R H S (Indian Horticulture, 2022)
High density planting (HDP) refers to increasing the plant population per unit area of land to increase the fruit production, overcome low productivity and long gestation period for early returns, which is achieved by using suitable scion varieties grafted on dwarfing/semi dwarfing rootstocks. High density orchards were first planted in Europe at the end of the 19th century and since then there is decline in traditional orchards with low densities. The underlying principle of HDP is to make the best use of vertical and horizontal space per unit time and to harness maximum possible return per unit of output. Standard apple plants raised on seedling rootstocks are planted at a spacing of 6×6 m to 7×7 m with a planting density of 204-278 trees/ha and spur varieties on seedling rootstocks are planted at a spacing of 5.0×5.0 m with a planting density of 400 plants/ ha. The average productivity of these orchards is approximately 10 to 12 MT/ha, which is much below the productivity obtained in high-density orchards (60-80 MT/ha). High-density planting of apple varieties grafted on dwarf/semi-dwarf clonal rootstocks can accommodate approximately 3,333 plants/ha to improve productivity without affecting the quality of the produce.